The Coming U.S. Interest Rate Tightening Cycle : Smooth Sailing or Stormy Waters? - Arteta, Carlos; Kose, M. Ayhan; Ohnsorge, Franziska; Stocker, Marc (World Bank, Washington, DC, 2015)
Since the global financial crisis, the exceptionally accommodative monetary policy stance of the U.S. Federal Reserve (Fed) has helped support activity, bolstered asset valuations, and reduced risk premia. In addition, it has been instrumental in boosting capital flows to emerging and frontier market economies (EFEs). As the U.S. economy improves, the Fed is expected to start raising policy interest rates in the near term (an event widely referred to as “liftoff”) and thus commence a tightening cycle for the first time in nearly a decade. The mid-2013 “taper tantrum” episode is a painful reminder that even a long-anticipated change in Fed policies can surprise markets in its specifics, and lead to significant financial market volatility and disruptive movements in capital flows to EFEs. Recent debates have focused on the potential impact of the liftoff on EFEs, but there are also significant risks associated with the pace of subsequent rate increases, which is currently expected to be very gradual, but could accelerate at a time when EFE policy buffers are eroding.